(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
A comparative analysis of the lawmaking policy between developed countries and Uzbekistan was founded. The study examined the legal reforms implemented in Uzbekistan after 2024 and their role in international cooperation. In particular, the processes of developing new laws and introducing technologies were analyzed. The differences between the lawmaking experience of developed countries and Uzbekistan’s approaches were also considered. The modernization of Uzbekistan’s legal system, reforms being implemented in accordance with international standards, as well as achievements and shortcomings in protecting individual rights were analyzed. The results show that Uzbekistan can use the experience of developed countries to further improve lawmaking.